Recruitment advertising for Antarctic personnel: between adventure and routine - Hanne Nielsen; Jaksic, C (2018)
This paper examines how Antarctica has been depicted in recruitment material, and compares the expectations set up in the advertising imagery with the reality of expeditioners’ experiences. Textual analyses of advertisements and job descriptions are used to reveal dominant themes, including the trope of extremity, while interviews with those who have spent time on the ice provide reflections on the actual challenges encountered when working in Antarctica, such as boredom. Much of the popular discourse around Antarctica continues to centre on the Heroic Era (1895–1922), a time of exploration typified by men pitting themselves against nature and striding out into unchartered expanses of ice. Although modern day life on Antarctic stations differs markedly from the extreme conditions experienced by early explorers, the continent continues to be associated with notions of toughness and extremity. We argue that in some cases, advertisements may actually target the wrong audience. This has important implications for how an Antarctic station as a workplace is conceptualised, and then experienced by those who head south, with potential detrimental effects.